Preparation and Characterization of Water Hyacinth Cellulose/ Keratose Composite Films - Chaosri, Patcharida; Srihanam, Prasong (Food Agricultural Sciences and Technology, 2020)
This research aimed to extract cellulose from water hyacinth for the preparation of composite films with different ratios of hair keratose. The keratose film has more transparency than other films. All films were then investigated their morphology, secondary structure, and thermal properties using scanning electron microscopy (SEM), Fourier transform infrared (FTIR) spectrophotometer, and Thermogravimetric analyzer (TGA), respectively. The results found that the native keratose film has smooth surfaces without phase separation, while the cellulose film has rough and some fibers appeared on its surface. The cellulose/keratose composite films have specific absorption peaks of each polymer functional groups. The secondary structure of the keratose film has a β-pleated sheet resulting in the fragile texture and brittle. Adding cellulose increased flexibility and thermal properties of the keratose film. This was due to the keratose and cellulose formed interaction via functional groups. The result suggested that cellulose and keratose are well compatible together. The finding results might be advantaged to use as basic information to prepare the cellulose/keratose composite films obtaining desire properties for applications.